Increasing Public Knowledge of the Importance of Protecting the Surrounding Environment in Sayang Sayang Market, Mataram City: Peningkatan Pengetahuan Masyarakat tentang Pentingnya Menjaga Kelestarian Lingkungan di Pasar Sayang Sayang, Kota Mataram - Baiq Ratih Widatari; Dea Kiki Amanda; Husnul Mawalia; Lalu Ismail Marzuki; Miqrazul Azahra; Tania Kiftiannisa (Yayasan Siti Widhatul Faeha, 2026)
Waste management in traditional market areas is still a significant environmental challenge in urban Indonesia. This service activity aims to increase public knowledge and awareness about the importance of maintaining environmental cleanliness in Sayang Sayang Market, Mataram City. The method used is direct counseling and socialization with an educational and participatory approach to 30 traders and market visitors on June 11, 2026. The results of the questionnaire showed that 88.7% of respondents had a high level of knowledge and concern for the environment, 96.7% knew the dangers of burning plastic, and 93.3% understood the risk of flooding due to piles of garbage. The results of the interviews confirm that the public is aware of the importance of market cleanliness for comfort and health. It is concluded that environmental education activities are directly effective in increasing the understanding of the market community, although there is still a need to strengthen facilities and continuous mentoring to encourage real behavior change.